Distance stereoacuity in intermittent exotropia. Issue 2 (2nd August 2006) - Hatt, S R; Haggerty, H; Buck, D; Adams, W; Strong, N P; Clarke, M P
Abstract : Background: Studies of distance stereoacuity in intermittent exotropia suggest that normal stereoacuity corresponds to good control of the deviation and that reduced or negative stereoacuity signifies poorer control. Aim: : To evaluate distance stereoacuity in intermittent exotropia using the Frisby Davis Distance stereo test (FD2). Methods: Children with intermittent exotropia where the near angle was less than or equal to distance were eligible for recruitment. Standardised prospective data collection included FD2 distance stereoacuity. This was a longitudinal study in which outcomes are reported for baseline, last follow-up (⩾6 months before any surgery) or preoperative and last postoperative visits for those undergoing surgery. Results: 110 children with intermittent exotropia had FD2 stereoacuity tested at baseline: 70 comprehended the test. Mean (standard deviation (SD)) age was 4.6 (1.7) years (range 2–10 years). 41/70 (59%) showed positive responses: mean (SD) stereoacuity 30 (12) s of arc. The mean follow-up period before any surgery was 13 months (range 6–27 months). At follow-up, mean (SD) stereoacuity was 24 (11) s of arc. Preoperative and postoperative stereoacuity were not significantly different from those not undergoing surgery. Conclusion: This study was the first to report distance stereoacuity in intermittent exotropia using the FD2 stereo test: patients with intermittent exotropia can achieve normal levels of distance stereoacuity, but a considerable proportion, despite comprehending, showed a negative response. This suggests that using the FD2, distance stereoacuity in intermittent exotropia is either absent or normal rather than reduced. Possible reasons for this and its implications are discussed.